Physical Aspects in The Feasibility Study of Revitalization For Merdeka Field in Medan - Dara Wisdianti (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This revitalization is carried out by reorganizing the function of space, and cultural values, and strengthening information about cultural heritage, as stated in Law Number 11 of 2010 concerning cultural heritage in article 80 paragraphs (1) and (2). Following the principle of development in general, revitalization must provide benefits to improve the quality of life of the community. This revitalization feasibility study uses primary data and secondary data. The results of the feasibility study on the revitalization of Merdeka Field Medan are the condition of the existing facilities and infrastructure of Merdeka Field, many of which are damaged or no longer functioning. There are even landfills in several corners of the Merdeka Square area. The drainage channels of the area are also not well integrated into the city's drainage system. And based on the problem of existing infrastructure, the Merdeka Square revitalization plan is very feasible to do.